Learning “Really Useful Knowledge:” Front-line Supervisors and Learning in Three Steel Mills - Ramo Lord; Fred Schied (Adult Education Research Conference, 2007)
Employing cultural historical activity theory (CHAT) this paper investigated of how informal learning is experienced by front line supervisors as they negotiate their role between two competing agendas.